Characterization of ascites in cardiac cirrhosis: the value of ascitic fluid protein to screen for concurrent cardiac cirrhosis. (3rd August 2017) - Wang, Yuchen; Attar, Bashar M.; Gandhi, Seema; Jaiswal, Palashkumar; Bedrose, Sara; Paranji, Neethi; Sharma, Sachit
Abstracts: Objectives: Cardiogenic ascites has been well described regarding its pathophysiology and fluid characteristics in prior literatures. However, ascites in patients with cardiac cirrhosis has not been characterized as a separate entity despite its unique pathophysiology and clinical aspects. This study aims to describe the fluid profile of ascites of cardiac cirrhosis and explore the utility of ascitic fluid protein (AFP) to predict concurrent cardiac cirrhosis. Methods and materials: We retrospectively selected and reviewed samples from the patients with cardiogenic ascites with and without concurrent cardiac cirrhosis. Epidemiologic characters, serum laboratory values, and fluid characteristics were directly compared between the groups. Results: We analyzed 20 samples of ascitic fluid from the patients of cardiac cirrhosis and compared with 48 samples of non-cirrhotic cardiac ascites. The AFP was significantly lower in patients with cardiac cirrhosis (3.66g/dl) as compared to non-cirrhotic patients (4.31g/dl, p < .01); while there was no difference in serum-ascites albumin gradient (1.48g/dl vs. 1.47g/dl, p = .95). AFP equal to or less than 4.3g/dl predicted cirrhosis with a sensitivity of 95% and negative likelihood ratio of 0.10; the corresponding ROC curve of AFP has an AUC of 0.777, higher than AUC of other noninvasive prediction models. Conclusions: We presented the first fluid characterization of ascites in patients with cardiac cirrhosis. AFP was significantly lower than that from non-cirrhotic cardiac ascites, likely secondary to decreased serum protein level. AFP equal to or less than 4.3g/dl could be utilized to screen for concurrent cardiac cirrhosis with high sensitivity in patients with cardiogenic ascites without other predisposing factors for liver injury.